PENGENDALIAN EROSI DI SUB DAS TEMON - , FAUZI HAMDAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Previous study in Temon Sub-Watershed indicated that land utilizations in this areas were not appropriate with their land functions, their land capabilities, and not adequate in applying soil conservation practices. This condition might cause water and soil resource degradation, as well as the decline of the catchment area quality. One of the methods to evaluate the decline of the catchment area quality is by using the approach of erosion prediction. Therefore, it was necessary to conduct a research to study the annual erosion. The objectives of the research were to predict the annual soil erosion of the area and to determine soil conservation practices in order to control the soil erosion. The research was conducted in Temon Sub-Watershed, in the area of Wonogiri regency, the province of Central Java. The research applied the USLE method to predict the erosion values (A). The base to determine soil conservation practices was conducted by comparing the erosion values (A) with the values of the tolerable soil erosions (T). The results of the research showed that the annual erosion of Temon Sub-Watershed was 85,83 ton/ha/year. The rice field contributed the lowest annual erosion at 0,24 ton/ha/ year , meanwhile the bare-land contributed the highest annual erosion at 969,34 ton/ha/jee year . Some areas of the Temon Sub-Watershed, which were 2355,36 ha (34 %) were under the values of the tolerable soil erosions (T)